If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3m*2=5m-3
We simplify the equation to the form, which is simple to understand
3m*2=5m-3
Simplifying:
+6m=5m-3
We move all terms containing m to the left and all other terms to the right.
+6m-5m=-3
We simplify left and right side of the equation.
+1m=-3
We divide both sides of the equation by 1 to get m.
m=-3
| 7.46=r-1.54 | | 7(m-9)-3(15m-4)=21 | | 3m/2=5m-3 | | 5g^2-2g-5=0 | | 10x(x-17)= | | 8=-2(x^2+1) | | 7m-63-45m+12=21 | | Y=-5x-0.6 | | y^2-7y-30= | | 8x+4=5x^2-5x-10 | | 6+3y= | | 5a*2=a+6 | | 15x+3y+2=0 | | 10x+6=54+9x | | x^2+10x=21 | | 5a+2=a*6 | | 5a+2=a/6 | | 5a/2=a+6 | | 5a+2=a+6 | | -1+9=5b-1-4b | | 4+2s=3(s+2)+1 | | 18a^5-6a^7= | | -4-2=6y+2-5y-3 | | 5(x+2)(x-1)=0 | | 2x+18+xy+9y= | | 3-3=17p-4p | | (b+3)*(b+8)= | | 3(20)-1= | | 21x^5+35x-9x^4-15= | | 4-7x=9-8x | | 2x(3+4y)-3=6 | | 4m(m-7)=0 |